Fossils from the Middle Jurassic of China shed light on morphology of Choristopsychidae (Insecta, Mecoptera) - Qiao, Xiao (2013)
Choristopsychidae, established by Martynov in 1937 with a single isolated forewing, is a little known extinct family in Mecoptera. Since then, no new members of this enigmatic family have been described. Based on 23 well-preserved specimens with complete body and wings from the Middle Jurassic of northeastern China, we report one new genus and three new species of Choristopsychidae, two new species of the genus Choristopsyche Martynov, 1937: C. perfecta sp. n. and C. asticta sp. n.; one new species of Paristopsyche gen. n.: P. angelineae sp. n.; and re-describe C. tenuinervis Martynov, 1937. In addition, we emend the diagnoses of Choristopsychidae and Choristopsyche. Analyzing the forewing length/width ratios of representative species in Mecoptera, we confirm that choristopsychids have the lowest ratio of forewing length/width, meaning broadest forewings. These findings, the first fossil choristopsychids with wellpreserved body structure and the first record of Choristopsychidae in China, shed light on the morphology of these taxa and broaden their distribution from Tajikistan to China, while increasing the diversity of Mesozoic Mecoptera in China.